2009
DOI: 10.1007/s00277-008-0676-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of human leukemia NB4 cells to increasing concentrations of selenite switches the signaling from pro-survival to pro-apoptosis

Abstract: Selenium at low concentrations has a chemopreventive role against cancer, while at high concentrations, selenite exerts a direct antitumor effect. However, the mechanisms behind these effects remain elusive. In this study, we found that different concentrations of selenite triggered different signal pathways in human leukemia NB4 cells. Low concentrations of selenite elicited mild endoplasmic reticulum (ER) stress and mediated cell survival by activating unfolded protein response signaling, whereas high concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Serum selenium concentrations provide prognostic implications because they can serve as a positive indicator for predicting effective dosage levels, optimum delivery routes, treatment response, and long-term survival [82]. The biology of cancer cells is modified by selenium based on it’s capacity to 1) induce apoptosis in doxorubicin-resistant lung small-cell carcinoma (selenite 10 μM) [46]; 2) promote severe ER stress (leukemia cell types) [83]; 3) reduce vitality of multidrug-resistant leukemia (selenitetriglycerides 10 μg/ml to 40 μg/ml) [84]; and 4) influence Fas signaling in MCF-7 mamary carcinoma in the presence of doxorubicin (methylseleninate 5 μM) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Serum selenium concentrations provide prognostic implications because they can serve as a positive indicator for predicting effective dosage levels, optimum delivery routes, treatment response, and long-term survival [82]. The biology of cancer cells is modified by selenium based on it’s capacity to 1) induce apoptosis in doxorubicin-resistant lung small-cell carcinoma (selenite 10 μM) [46]; 2) promote severe ER stress (leukemia cell types) [83]; 3) reduce vitality of multidrug-resistant leukemia (selenitetriglycerides 10 μg/ml to 40 μg/ml) [84]; and 4) influence Fas signaling in MCF-7 mamary carcinoma in the presence of doxorubicin (methylseleninate 5 μM) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Because of these selective effects on tumor cells, it would be exciting to explore whether selenite can induce specific downregulation of HLA-E on tumor cells in vivo, while preserving its expression on normal cells and thereby preventing NK cell targeting of normal HLA-E-expressing tissues. Besides its effects on HLA-E, selenite is also an attractive drug candidate because of its other anti-tumor properties, including inhibition of cellular growth and induction of DNA strand breaks leading to apoptosis (35)(36)(37)(38)59). In fact, one recent study showed that low concentrations of selenite were more cytotoxic to primary AML blast cells than were conventional drugs (60), and several other studies have indicated that selenite is especially cytotoxic in tumor cells that are resistant to conventional drugs (34,40).…”
Section: Discussionmentioning
confidence: 99%
“…Low dietary intake of selenium has been associated with an increased incidence of prostate cancer (29), whereas supplementation has been linked to reduced risk for cancers such as skin and liver cancer (30)(31)(32). Interestingly, the inorganic selenium compound selenite (SeO 3 22 ) has been shown to induce apoptosis in a wide range of solid tumor cells (33)(34)(35)(36) and various hematological malignancies (37,38), with a selective cytotoxic effect on malignant cells compared with normal cells (39)(40)(41). Selenite can also hit drug-resistant tumor cells (33,42) and potentiate the effect of some chemotherapeutic drugs (35,43).…”
mentioning
confidence: 99%
“…On the other hand, use of selenium-cystine (as diseleno-dialanine) in leukemic patients decreased total leukocyte count, immature leukocytes in CML and AML patients (17). Anti-leukemic effect of sodium selenite (Na 2 SeO 3 ) was suggested to activate p53 to cause apoptosis (18–24). However, the mechanism by which selenium activates p53 is not well understood.…”
Section: Introductionmentioning
confidence: 99%